Managing Sustainable Performance and Governance in Higher Education Institutions A Dynamic Performance Management Approach - Cosenz, Federico (Cham : Springer International Publishing : Imprint: Springer, 2022)
The fast-changing evolutionary process of global Higher Education systems systematically poses new challenges related to the appearance of innovative elements that lead academic governing bodies to question current managerial structures and methods. Due to this, theory and practice have gathered multiple contributions and experiences to support and further develop this evolutionary pathway during the past decades. Global competitiveness, economic and social growth are driven worldwide by knowledge and innovation. In this context, Higher Education Institutions play a crucial role as they primarily contribute to knowledge transfer and development and, as a result, foster regional development, employment, and economic wealth. The relevance of this role leads Universities to explore alternative solutions for managing their performance according to a sustainable perspective.This book draws on this flourishing debate on Higher Education policy and management and investigates an innovative systemic perspective to design and implement sustainable performance management systems for academic institutions. The conditions for the success of Universities, the critical issues underlying the creation of academic value, the dynamic complexity characterizing academic governance settings, the pluralistic audience of stakeholders and related expectations, the causal interplays between organizational performance variables, represent some of the central themes around which this work is developed. More specifically, the book suggests and discusses the adoption of a Dynamic Performance Management approach to frame the inherent organizational complexity of Higher Education Institutions, thus supporting a strategic learning perspective to design and implement relevant performance measures. This approach originates from the combination between conventional performance management and System Dynamics modeling. Many research and practice contributions prove that this methodological combination can boost the understanding and interpretation of value creation processes by identifying and exploring the causal connections amongst strategic resource allocation and consumption, corresponding performance drivers, emerging outputs, and outcomes. To test the effectiveness of this approach in University settings, a wide range of examples is offered in each book chapter. This allows readers to explore the advantages, limitations, and practical implications of adopting Dynamic Performance Management in Higher Education Institutions, as well as guide academic decision-makers towards a more robust approach to design and implement strategic management mechanisms in Universities.
Chapter 1. Performance Systems in Higher Education Institutions -- Chapter 2. Developing Performance Management Systems in Higher Education Institutions -- Chapter 3. Designing Dynamic Performance Management Systems in Higher Education Institutions -- Chapter 4. University "Third Mission" Assessment Through Outcome-Based Dynamic Performance Management -- Chapter 5. Conclusions.
Keywords: Education, Higher; Public administration; Project management; Higher Education; Public Administration; Project Management; Public Management